Exploring the mechanisms of Gui Zhi Fu Ling Wan on varicocele via network pharmacology and molecular docking. (13th November 2022) - Wang, Ruipeng; Qiao, Xiaoye; Wang, Xiaobin
Abstract: Varicocele (VC) is a common urogenital disease that leads to a high risk of testicular pain or male infertility. The purpose of this research was to explore the molecular mechanism of the Gui Zhi Fu Ling Wan (GFW) in the treatment of VC. The main active ingredients and targets information of GFW were screened by Traditional Chinese Medicine Systems Pharmacology (TCMSP) database, and the targets related to VC were determined by GeneCards, Online Mendelian Inheritance in Man (OMIM), and Disease Gene Network (DisGeNET) databases. The intersection of active ingredient targets and disease targets was selected to construct a protein–protein interaction (PPI) network through the Search Tool for the Retrieval of Interacting Genes/Proteins (STRING) database. Based on the use of CytoNCA plug‐in to find the main targets, a 'component‐target‐disease' network was constructed by Cytoscape 3.8.2. Metascape was used for Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses of drug and disease targets. Molecular docking was employed to investigate the binding interaction between the main active components and core targets. A total of 76 active components of GFW were screened out. The main targets of the active components on VC were tumour protein p53 (TP53), tumour necrosis factor (TNF), hypoxia inducible factor 1 subunit alpha (HIF1A), interleukin‐6 (IL‐6), caspase 3 (CASP3), catalase (CAT), prostaglandin‐endoperoxide synthase 2 (PTGS2), vascular endothelial growth factor A (VEGFA). The PI3K‐Akt signalling pathway, HIF‐1 signalling pathway, and apoptosis signalling pathway were mainly involved in the regulation of VC. The results of molecular docking showed that the binding potential and activity of the main active components and the core targets of GFW were good. We found that GFW could alleviate apoptosis, participate in venous vessel morphogenesis, and reduce oxidative stress in the treatment of VC. This study can provide a reference for subsequent clinical and scientific research experiments, which can be used to design new drugs and develop new therapeutic instructions to treat VC.